Slip Flow Coefficient Analysis in Water Hydraulics Gear Pump For Environmental Friendly Application - Yusof, Ahmad Anas; Wasbari, Faizil; Mohamad Shukri , Zakaria; Ibrahim, Mohd Qadafie (IOP Publishing, 2013)
Water hydraulics is the sustainable option in developing fluid power systems with environmental friendly approach. Therefore, an investigation on water-based external gear pump application is being conducted, as a low cost solution in the shifting effort of using water, instead of traditional oil hydraulics in fluid power application. As the gear pump is affected by fluid viscosity, an evaluation has been conducted on the slip flow coefficient, in order to understand to what extend the spur gear pump can be used with water-based hydraulic fluid. In this paper, the results of a simulated study of variable-speed fixed displacement gear pump are presented. The slip flow coefficient varies from rotational speed of 250 RPM to 3500 RPM, and provides volumetric efficiency ranges from 9 % to 97% accordingly.